Pengaruh Kompensasi Finansial Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Andalas Surya Jaya Medan - Loren Simbolon; Emma Novirsari; Debora Tambunan (CV. ULIL ALBAB CORP, 2024)
PT. Andalas Surya Jaya Medan, the reason for the selection of objects is due to a decline in employee performance in the company. The decline in employee performance is caused by the lack of compensation provided by the company to employees and the inappropriate provision of compensation for the educational background and position of employees in the company which causes employees to feel dissatisfied, as well as the lack of employee discipline at work, the presence of employees who are late at work and the frequency of employees making mistakes at work so that it has an impact on the work results of employees who are is declining. The theories used in this study are human resource management theories, which are related to financial compensation, work discipline and employee performance. The analysis methods used are multiple linear regression, simultaneous test determination coefficient (F-test), and partial test (t-test). The results of the study on the hypothesis show that financial compensation and work discipline simultaneously and partially have a significant effect on employee performance with a determination coefficient value of 0.645 which shows that financial compensation and work discipline have an effect on employee performance with a percentage rate of 64.50% while the remaining 35.50% are other factors that have not been researched such as leadership, motivation and competence. Based on the overall results of the study, it can be concluded that financial compensation and work discipline affect employee performance at PT. PT. Andalas Surya Jaya Medan